PEMBERDAYAAN SUMBER DAYA MANUSIA, RESILIENSI ORGANISASI, DAN KINERJA ORGANISASI PADA INDUSTRI JASA - Triatmanto, Boge (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2011)
Objective of the research was to examine empirically the influence of human resources empowerment, directly and indirectly, through organization resilience on an organization performance. Objectives of the research in detail were to analyze and examine empirically the influences of: human resources empowerment on organization performance, human resources empowerment on organization resilience, and organization resilience on organization performance. Population of the research was 69 star hotels, which spread over the East Java Province. 34 hotels were taken as samples. The respondents were 216 managers. Samples were taken using proportional sampling method and data analysis of the research used SEM (Structural Equation Model). The main finding of this research was that the organization performance would be enhanced if the human resources were empowered in participating to achieve the organization goal, commit to the organization, and have greater authority and responsibility in decision-making process. This influence will be stronger if it is followed by the organization capability to adapt to any change at the organization environment.